2012
DOI: 10.1097/yct.0b013e318238f01a
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Adolescents With Resistant Depression Treated With Repetitive Transcranial Magnetic Stimulation

Abstract: Preliminary evidence suggests that rTMS treatment of resistant depression in adolescents is not associated with long-term cognitive deterioration and that posttherapy clinical improvement can be maintained. It seems that some subjects may derive long-term benefit from the rTMS course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…From the same sample, 8 of these study participants were followed for 3 years, and found that no cognitive deterioration occurred and some subjects maintained clinical improvement after treatment [51]. Wall et al [52] followed 7 of 8 adolescents in an open trial of rTMS for 6 months, and found rTMS to be safe and was the preferred treatment over medication for the majority of patients and their parents.…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 99%
“…From the same sample, 8 of these study participants were followed for 3 years, and found that no cognitive deterioration occurred and some subjects maintained clinical improvement after treatment [51]. Wall et al [52] followed 7 of 8 adolescents in an open trial of rTMS for 6 months, and found rTMS to be safe and was the preferred treatment over medication for the majority of patients and their parents.…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 99%
“…Gillick et al (2014a) and Mayer et al (2012) reported no serious adverse events following rTMS in children. However, long-term outcomes have not yet been reported on studies combining NIBS with motor interventions in children with hemiparesis.…”
mentioning
confidence: 99%
“…Long-term safety and efficacy is evident in CIMT (Olesch et al 2010;Eliasson and Holmefur 2015). Safety of CIMT in children is measured by monitoring for functional decline in the restrained limb and parental stress (Cope et al 2008;Fedrizzi et al 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations